2014
DOI: 10.1155/2014/301386
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Effect of High-Molecular Weight Poly-Gamma-Glutamate against Newcastle Disease Virus on Murine Macrophage Cells

Abstract: This study demonstrates the capacity of HM-γ-PGA treatment to significantly protect murine macrophage cells (RAW 264.7 cells) against NDV infection. Such protection can be explained by the induction of antiviral state of HM-γ-PGA in RAW 264.7 cells via TLR4-mediated IRF-3, IRF-7, IFN-β, and IFN-related gene induction as shown in time-dependent changes in mRNA expression confirmed by polymerase chain reaction (PCR). Moreover, the present research also showed that HM-γ-PGA can induce proinflammatory cytokine sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…HT29 and HCT116 cells were cultured in McCoy's 5 A medium (Sigma Aldrich, St. Louis, MO) containing 10% heat-inactivated foetal bovine serum (HI-FBS) (Gibco, USA), 100 μg/mL streptomycin (Invitrogen, USA), and 100 mg/ml penicillin (Invitrogen, USA) 40 . HCA7 and RAW 264.7 cells were cultured in Dulbecco's minimal essential media (DMEM, Invitrogen) containing 10% HI-FBS, sodium pyruvate (1 mM), penicillin (100 mg/mL), and streptomycin (100 mg/m) 41 , 42 .…”
Section: Methodsmentioning
confidence: 99%
“…HT29 and HCT116 cells were cultured in McCoy's 5 A medium (Sigma Aldrich, St. Louis, MO) containing 10% heat-inactivated foetal bovine serum (HI-FBS) (Gibco, USA), 100 μg/mL streptomycin (Invitrogen, USA), and 100 mg/ml penicillin (Invitrogen, USA) 40 . HCA7 and RAW 264.7 cells were cultured in Dulbecco's minimal essential media (DMEM, Invitrogen) containing 10% HI-FBS, sodium pyruvate (1 mM), penicillin (100 mg/mL), and streptomycin (100 mg/m) 41 , 42 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, oral administration of γ-PGA in a mouse model increased the production of IFN-β levels in the serum without any noticeable effect on other inflammatory cytokines, whereas it reduced norovirus loads in the ileum. Other studies have also shown that high molecular weight γ-PGA has been reported to have antiviral function against Newcastle disease virus (NDV) (Talactac et al, 2014 ). High molecular weight γ-PGA inhibited NDV replication and decreased apoptosis mediated by virus infection in RAW264.7 cells.…”
Section: Bacillus Subtilis Chungkookjang (Poly-γ-glutamate γ...mentioning
confidence: 99%
“…chungkookjang was prepared and provided by BioLeaders Corporation (Daejeon, Korea) in 0.85% sterile NaCl solution, as described in previous studies [3,7,9]. Briefl y, the culture broth of B. subtilis subsp.…”
Section: Preparation Of Hm-γ-pgamentioning
confidence: 99%
“…Previous studies have also demonstrated that HM-γ-PGA had antiviral activity. HM-γ-PGA exerts signifi cant antiviral activity that can inhibit Newcastle disease virus infection by stimulating an antiviral state on RAW 264.7 cells [9]. Additionally, previous studies have shown that treatment with infl uenza inhibitors (polyvalent sialidase inhibitors) on the γ-PGA backbone may have antiviral activity against Infl uenza A virus [10].…”
Section: Introductionmentioning
confidence: 99%